Breather Interaction Properties Induced by Self-Steepening and Space-Time Correction *Supported by the National Natural Science Foundation of China (Grant Nos. 11705145, 11947301, 11434013, and 11425522), the Major Basic Research Program of Natural Science of Shaanxi Province (Grant Nos. 2017KCT-12 and 2017ZDJC-32), and the Natural Science Basic Research Plan in Shaanxi Province of China (Grant No. 2018JQ1003). (13th April 2020) - Wu, Yu-Han; Liu, Chong; Yang, Zhan-Ying; Yang, Wen-Li
Abstract: We study the properties of breather interactions in nonlinear Kerr media with self-steepening and spacetime correction and with either self-focusing or self-defocusing nonlinearity, and present a new family of exact breather solutions via the Darboux transformation with a special-designed quadratic spectral parameter. In contrast to the previous results of the nonlinear Schrödinger equation (NLSE) hierarchy, we show that the relative phase of colliding breathers has a significant effect on the collision manifestation. In particular, only the out-of-phase interactions can generate small amplitude waves at the collision center, which are analogous to the NLSE super-regular breathers. Our results will deepen our understanding of the properties of breather interactions and they will offer the possibility of experimental observations of super-regular breather dynamics in systems with self-steepening and spacetime correction.